Was Boris Vipper Mistaken? - Evsevyev, Mikhail Iu. (Actual Problems of Theory and History of Art, 2016)
In 1946  Boris Vipper wrote an article entitled Silvester Schedrin in Italy which was published in the Soviet Art History magazine only in 1975. In this paper he defined a Neapolitan artist Raffaele Carelli (1795–1864) to be Schedrin’s “teacher and inspirator”. We do not know why Vipper thought that Carelli died young in 1815. This wrong fact in the artist’s biography had a strong impact on Vipper’s implications. In the art historian’s opinion Carelli seems to be “a talented predecessor of Schedrin and the forerunner of En plein air in European painting of the 19th century”. In this case, Neapolitan landscapes by Carelli must have been created earlier than similar works of Schedrin, because Russian artist appeared in Naples only in 1819. This fact forced Vipper to decide that Carelli had great influence on Schedrin’s painting style. Nevertheless, the art historian noted artistic superiority of Schedrin’s landscapes in comparison with Carelli’s works. There are no authentic pieces of art by Carelli dated earlier than 1833. That is why it is clear that Carelli worked as an artist in the middle of the 19th century. Therefore, Carelli either could see some works of Schedrin or was a skillful follower of the Neapolitan landscapists’ manner of the 1830s. It is not surprising that details of Carelli’s biography were forgotten; after all, he was a second-rate artist even in comparison with other artists of the Neapolitan landscape school of the 19th century. Probably he realized that fact himself. Carelli was exhibited for the last time in 1835, after that he gave up art and got into teaching and antique-trade.
Keywords: S. F. Shchedrin; R. Carelli; B. R. Vipper; Italy; Russia; landscape painting; Italian painting; Russian art; 19th century; “School of Posillipo”